2022
DOI: 10.1111/jonm.13648
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nurses' roles and burden on burnout during the COVID‐19 pandemic: Multicentre cross‐sectional survey

Abstract: Aim To identify groups of nurses engaging in coronavirus disease (COVID‐19) care who are most in need of organizational support. Background Overwhelming stress and susceptibility to burn‐out have been reported in nurses during the COVID‐19 pandemic. Methods Nurses working at five hospitals which accepted COVID‐19 patients answered the questionnaire. The Tokyo Metropolitan Distress Scale for Pandemic, Self‐Diagnosis Check List for Assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Correspondingly, an increase in psychological and physical stress has been associated with increased burnout among Japanese nurses, resulting in a higher incidence of burnout. These nurses provide direct care to patients hospitalized for observation suspected of having COVID‐19 infection (Kishi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, an increase in psychological and physical stress has been associated with increased burnout among Japanese nurses, resulting in a higher incidence of burnout. These nurses provide direct care to patients hospitalized for observation suspected of having COVID‐19 infection (Kishi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study was conducted during the COVID‐19 pandemic, a period during which frontline nurses are facing significant difficulties in carrying out their nursing roles and responsibility. Published studies on burnout during the COVID‐19 pandemic reported burnout's influence on nurses' intention to leave (de Cordova et al, 2022 ), burnout during the first wave of the pandemic (Galanis et al, 2021 ; Khan et al, 2022 ), burnout on quality patient care (Kakemam et al, 2021 ), burnout and the affective aspect of nurses (Falatah & Alhalal, 2022 ), burnout's burden to nurses' roles (Kishi et al, 2022 ) and burnout's relationship to self‐efficacy (Lim et al, 2022 ). None of these published studies focused on the moderating effect of burnout on nurses' professionalism, values and competence.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the impact of the subject under analysis, which has been demonstrated in several studies, one of the highlighted aspects is the extreme physical and emotional demands requested from nurses. It is not surprising that there has been a growing number of studies on this topic about the magnitude of burnout during the pandemic because of the increased demand from all professionals [ 35 , 36 , 37 ]. That is why it is necessary to know this reality and create mechanisms that minimize its impact so that we are prepared as much as possible to respond to it, especially in situations where its incidence increases considerably [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies around the globe had emphasized similar emotional outcomes of the pandemic. For example, Kishi H et al (2022) analyzed 895 questionnaires of nurses' Accumulated Fatigue and Japanese Burnout Scale and found signi cant relationship between engaging in COVID-19 care and psychosocial/physical burden particularly in the form of distress, emotional fatigue, emotional exhaustion and burn out risks. Whereas Molina-Mula J et al (2022) survey of 892 Spanish nurses con rmed the presence of emotional fatigue (OR 1.9, p < 0.001), anxiety, moderate post-traumatic stress evident in general nurses, and severe post-traumatic stress evident in ICU nurses.…”
Section: Discussionmentioning
confidence: 99%